Caracterização demográfica e epidemiológica de cães e gatos domiciliados: Barbacena, Minas Gerais - 2006 - Marcio Heitor Stelmo da Silva (2007)
This paper presents the characterization of the canine and feline population in Barbacena county, 2006. Data were obtained by semi-structured questionnaire application performed in 840 propertiesdetermined by random sampling. Data were processed in software EPIInfo version 6.04. Results revealed the existence of 0.216 dogs per habitant, 0.051 cats per habitant, 0.805 dogs per property, 0.190 cats per property. Dogs are present in 51.3% of the property total, in 77.9% of them rural and 48.6% urban. Of these, in 47.3% of the houses and in 16.5% of the apartments. Cats are present in 12.5% of the property total, in 31.2% of the rural properties and in 10.6% of the urban ones. Ofthese, in 11.2% of the houses and in 5.9% of the apartments. Regarding to the age of the animals, it was found an average of 4.47 years for dogs and 2.90 years for cats. Male/female proportion was 1.58 for dogs and 0.905 for cats. It was verified 0.26 labors per female dogs and 3.07 puppies per labor; 0.417 labors per female cat and 2.9 kitties per labor. Mortality until weaning was 13.4% in dogs and 22.8% in cats. In regards to the breed, it was observed that 41.9% of the dogs and 55.6%of the cats do not have a defined breed. For fellowship purposes, it was found a percentage of 68.3% dogs and 99.4% cats. 4.14% of the dogs have come from other counties. 65.8% of the dogs and 65.6% of the cats were received from adoption. Considering the type of food, 55.9% of the dogs and 46.3% of the cats fed exclusively of industrialized products. 29.6% of the dogs and 16.5% of the cats were attended by a Veterinarian. 13.3% of the dogs and 3.8% of the cats got sick at that year. 58.5% of the dogs and 38.1% of the cats were treated with worm medicines. There was a daily collection of faeces of 76.9% of the dogs and 49.9% of the cats. Anti-rabies vaccine and other vaccines cover was respectively 89.2% and 40.1% for dogs and 68.1% and 21.6% for cats. 8.1% of the female dogs and 17.9% of the female cats were castrated or received anti conception treatment. 43.8% of the dogs and 18.1% of the cats live confined and 28.1% of the dogs and 79.4% of the cats are not confined. It may be concluded that the canine and feline population was superior than the estimative performed by the local Health Service, being largethe amount of dogs walking throughout the streets of the county headquarter in disagreement with the municipal legislation, besides most of the canine population be managed according to the same legislations